The Legal Regulation of Cybercrime in the United States of America Legislation - MOISE, Adrian Cristian (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
This article presents the main cybercrime legislation in the United States of America law and how the provisions of the Council of Europe Convention on Cybercrime were incorporated into the Federal Criminal Code. It also emphasized that the United States of America legislation includes other offences that are not provided under the Council of Europe Convention on Cybercrime.